2021
DOI: 10.3389/fpsyg.2021.642956
|View full text |Cite
|
Sign up to set email alerts
|

Passion and Persistence: Investigating the Relationship Between Adverse Childhood Experiences and Grit in College Students in China

Abstract: Adverse childhood experiences (ACEs) are known to have deleterious effects on individuals across the life span, but less is known about how they affect grit, a strong predictor of achievements and well-being. This study seeks to investigate the effect of ACEs on grit in a sample of Chinese college students during the COVID-19 pandemic. Data were collected from 1,871 students across 12 universities in China. Findings indicated a significant effect of ACEs on grit, particularly abuse and neglect dimensions of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…Using a sample of 2,073 medical college students in Anhui province, Xiao et al (14) described that more than two-thirds (68.9%) of participants experienced at least one type of ACEs, among which physical neglect (26.9%), physical abuse (26.7%), and mental illness in the household (23.0%) comprised the greatest portions. Subsequently, a number of studies estimated the prevalence of ACEs in China (13,(15)(16)(17)(18). Though fluctuating, the rate of ACEs in China is between 35.2-75.0%.…”
Section: Aces Research In Chinese Populationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a sample of 2,073 medical college students in Anhui province, Xiao et al (14) described that more than two-thirds (68.9%) of participants experienced at least one type of ACEs, among which physical neglect (26.9%), physical abuse (26.7%), and mental illness in the household (23.0%) comprised the greatest portions. Subsequently, a number of studies estimated the prevalence of ACEs in China (13,(15)(16)(17)(18). Though fluctuating, the rate of ACEs in China is between 35.2-75.0%.…”
Section: Aces Research In Chinese Populationsmentioning
confidence: 99%
“…Most ACE studies, both Chinese and international, examined ACEs using cumulative risk scores and found dose-dependent relationships with studied outcomes [e.g., (20)(21)(22)(23)(24)]. Recently, a growing number of studies evaluated the effects of ACEs by category and presented some evidence that different categories of ACEs might have distinct outcomes (17,(25)(26)(27). For instance, Anonymous (17) surveyed a college sample from China and found that the abuse/neglect category was related to poorer grit, while household challenges were associated with increased consistency.…”
Section: Aces Research In Chinese Populationsmentioning
confidence: 99%
See 3 more Smart Citations